Automatic evaluation of UV and R2 terms for beyond the Standard Model Lagrangians: A proof-of-principle - Degrande, Celine (Computer physics communications, 2015)
The computation of renormalized one-loop amplitudes in quantum field theory requires not only the knowledge of the Lagrangian density and the corresponding Feynman rules, but also that of the ultraviolet counterterms. More in general, and depending also on the method used in the actual computation of the one-loop amplitudes, additional interactions might be needed. One example is that of the R2 rational terms in the OPP method. In this paper, we argue that the determination of all elements necessary for loop computations in arbitrary models can be automated starting only from information on the Lagrangian at the tree-level. In particular, we show how the R2 rational and ultraviolet counterterms for any renormalizable model can be computed with the help of a new package, which we name NLOCT and builds upon FeynRules  and FeynArts. To show the potential of our approach, we calculate all additional rules that are needed to promote a Two Higgs Doublet Model Lagrangian to one-loop computations in QCD and electroweak couplings. Program title: FeynRules-2.1 with NLOCT Catalogue identifier: AEDI_v2_1 Program summary URL:http://cpc.cs.qub.ac.uk/summaries/AEDI_v2_1.html Program obtainable from: CPC Program Library, Queen’s University, Belfast, N. Ireland Licensing provisions: Standard CPC licence, http://cpc.cs.qub.ac.uk/licence/licence.html No. of lines in distributed program, including test data, etc.: 58179 No. of bytes in distributed program, including test data, etc.: 506216 Distribution format: tar.gz Programming language: Mathematica. Computer: Platforms on which Mathematica is available. Operating system: Operating systems on which Mathematica is available. Classification: 11.1, 11.6. Catalogue identifier of previous version: AEDI_v2_0 Journal reference of previous version: Comput. Phys. Comm. 185(2014)2250 External routines: FeynArts-3.7 or above Does the new version supersede the previous version?: Yes Nature of problem: The new version of FeynRules renormalizes and computes with the new NLOCT package the ultraviolet counterterms and the rational R2 terms induced by one-loop amplitudes. The resulting vertices can be exported in the UFO format to event generators such as MadGraph5_aMC@NLO. Solution method: First, the Lagrangian is renormalized in FeynRules and exported to FeynArts through the corresponding interface. Secondly, the NLOCT package computes the R2 and UV vertices using the amplitudes from FeynArts. Finally, the list of NLO vertices is loaded in FeynRules to be exported in the UFO format. Reasons for new version: The new version allows the automated generation of any model in the UFO format with all the required ingredients to perform automatically one-loop computation. Summary of revisions: This new version contains all the elements to perform the computation of the NLO ingredients: A function to perform the renormalization in FeynRules, the NLOCT package computes of the UV and R2 vertices and the extended UFO interface adds them in the output. Restrictions: The model should be renormalizable, i.e. the dimension of the operators should not exceed four, and written in the Feynman gauge. Running time: The running time ranges from a few minutes for models like the SM to a few hours for more complicated models like the MSSM.